Analysis of the essential oils from Calendula officinalis growing in Brazil using three different extraction procedures (Revista Brasileira de Ciências Farmacêuticas, 2008)
Terpenes and aroma volatiles from flowers of Calendula officinalis cultivated in southeastern Brazil were obtained by steam distillation (SD), headspace-cold finger (HS-CF) extraction and headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography and mass spectrometric analysis. The dried flowers contained 0.1% oil. Kovats indices and mass spectra were used to identify 27 individual components in the various volatile fractions. The main components present in the volatile fractions of the C. officinalis flowers, obtained by SD, HS-SPME, and HS-CF, were δ-cadinene (22.5, 22.1, and 18.4 %) and γ-cadinene (8.9, 25.4, and 24.9 %) while 20.4 % of α-cadinol was seen only after SD extraction.